Performance of Low Power Electric Energy Clothes Dryers for Households - Doddy Purwadianto; Budi Sugiharto (Universitas Sanata Dharma, 2023)
One of the problems faced by middle to lower economic class people in big cities is drying clothes, both in the dry season and in the rainy season. Artificial clothes drying equipment is needed that can replace the role of solar energy. The purpose of this study was to determine the performance of electric energy clothes dryers and the length of time needed to dry clothes on a household scale. The clothes dryer works by using a heat-pump based on the vapor-compression cycle. The total power of the heat pump is 200 watt. The working fluid of the heat-pump is R134a. The working fluid used to dry clothes is air, using a closed airflow system. The research was carried out experimentally by varying the amount of clothes in the drying chamber. The clothes dryer performance (COP) of the heat pump is 7.94. Drying time for 15, 25 and 40 clothes respectively for 210 minutes, 330 minutes and 450 minutes.